Keterkaitan Jenis, Jenjang Pendidikan Dan Masa Kerja Terhadap Kemamapuan Mengajar Guru Mata Pelajaran Ekonomi Pada SMA/MA Di Kota Ende - Yosef Moan Banda (Ekspektasi: Jurnal Pendidikan Ekonomi, 2016)
Linkage Type, Level of Education and Teaching Ability To Work Period Subject Teacher of Economics at SMA / MA in Kota Ende, 2016.This study aimed to obtain information about the linkage type, Study of Education and Work Period to the ability to teach Master of Economics in SMA / MA in Kota Ende. The aspects examined included: Linkages ability to teach Master, level, type of education and teacher tenure. This research is a type of survey, with a population of economics teachers SMA / MA in Kota Ende 20 people, while the sample is 5 teachers economics class XI. The samples in this study conducted rendom sampling that a lottery system because all have the same opportunities. The instrument used for data collection in the form of observation sheets and questionnaires. Validation of instruments made by expert's judgment.dan consultation with colleagues. Data were analyzed with descriptive quantitative and qualitative techniques.The results showed that the ability of teachers to teach economic subjects in the city of Ende related to the type and tenure of teachers who have the ability tinggi.Sedangkan levels of education not berpengaruhterhadap teaching capabilities.